PENGARUH MODEL QUICK ON THE DRAW TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI MENGIDENTIFIKASI INFORMASI TEKS LAPORAN HASIL OBSERVASI - Zaki Fahrizal (Universitas Islam Negeri Mataram, 2022)
The purpose of this study was to determine the effect of the Quick on The Draw model on student learning motivation and student learning outcomes in the basic competence of identifying text information on observation reports. The method used is a quasi-experimental method with a pretest-posttest control group design. The independent variable in this study is the Quick on The Draw model while learning motivation and student learning outcomes are the dependent variable. The population in this study were students of class VII MTsN 4 Tangerang, Academic Year 2022-2023 with a sample of class VII.1 students as the control class and students of class VII.2 as the experimental class. The sampling technique is simple random sampling. Data collection was carried out using multiple choice written tests to measure student learning outcomes and student motivation questionnaires to determine student motivation. Based on the results of the study, learning motivation and student learning outcomes in the experimental class were higher than those in the control class with a significance value (0.000 <0.05). Based on the results of the t-test analysis, it can be concluded that there is an influence of the Quick on The Draw model on learning motivation and student learning outcomes in the basic competencies of identifying information in the text of observation reports.